Aktivitas Antioksidan Ekstrak Buah Mengkudu (Morinda citrifolia, L) - Abdul Rohman; Sugeng Riyanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2005)
This research aimed to determine antioxidant activity of Morinda citrifolia, L fruit extracts. Morinda citrifolia, L fruit was ground, extracted by methanol, and partitioned by using chloroform and ethyl acetate to recover extracts of methanol, chloroform and ethyl acetate respectively. These extracts were diluted to various concentrations i.e. 1, 5, and 10 %, and were determined their antioxidant activities by linoleic-thiocyanate method. The result showed that extracts of Morinda citrifolia, L fruit had antioxidant activity in the order of ethyl acetate extract > chloroform extract > methanol extract. Antiradical activity tests were carried out by using DPPH (2,2-dipheny1-1-piaylhydrazil) method, the results showed that ethyl acetate extract, chloroform extract, and methanol extract revealed IC50 46,7, 227,7 and 888,6 pg/ml, respectively.